A two-dimensional Bi2O2Se single crystal with biaxial tensile strain and preparation method thereof

The preparation of two-dimensional Bi2O2Se single crystals on a specific substrate by chemical vapor deposition method solves the problem of difficult to achieve high strain rate and yield rate in the prior art, and efficient preparation of biaxial tensile strain of up to 2.8 to 8%, confirms the strain ferroelectricity and improves repeatability.

CN117737859BActive Publication Date: 2025-03-18WUHAN UNIV OF TECH +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311765497.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-20
Publication Date
2025-03-18
Estimated Expiration
2043-12-20

AI Technical Summary

Technical Problem

It is difficult to prepare two-dimensional Bi2O2Se single crystals with high biaxial tensile strain in the prior art, and the generation of strains has problems such as sample damage and poor repeatability.

Method used

A two-dimensional Bi2O2Se single crystal was prepared on MgO or SrTiO3 substrate by chemical vapor deposition. By adjusting the deposition conditions and substrate design, the biaxial tensile strain of the two-dimensional Bi2O2Se single crystal was achieved at 2.8 to 8%.

Benefits of technology

The high strain rate and high yield rate of two-dimensional Bi2O2Se single crystal were achieved, the sample damage was reduced, and the repeatability was excellent, and the strain ferroelectricity of two-dimensional Bi2O2Se was confirmed.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117737859B_ABST
    Figure CN117737859B_ABST
Patent Text Reader

Abstract

The present invention relates to a two-dimensional Bi2O2Se single crystal with biaxial tensile strain and a preparation method thereof, wherein the two-dimensional Bi2O2Se single crystal with biaxial tensile strain has a square nanosheet structure, the square nanosheets are arranged and grown in a parallel manner, and the biaxial tensile strain is 2.8-8%. The biaxial tensile strain of the two-dimensional Bi2O2Se single crystal provided by the present invention is as high as 2.8-8%, and the sample exhibits ferroelectricity predicted in theoretical research, and has broad application prospects in ferroelectric storage materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of manufacturing or processing of nanostructures, and specifically relates to a two-dimensional Bi2O2Se single crystal with biaxial tensile strain and a preparation method thereof. Background Art

[0002] As an emerging two-dimensional functional material, two-dimensional Bi2O2Se has the advantages of ultra-high carrier mobility, low thermal conductivity, variable band gap width, excellent air stability, etc., and has great potential in the fields of thermoelectricity, electronics, optoelectronics, etc. At present, the preparation of two-dimensional Bi2O2Se is mainly carried out by chemical vapor deposition on a mica substrate with similar structure. The grown two-dimensional Bi2O2Se single crystals mainly present square or rectangular nanosheet structures with thickness ranging from a few nanometers to tens of nanometers. In the chemical vapor deposition preparation of two-dimensional Bi2O2Se single crystals, due to the good diffusion of the precursor vapor on the mica substrate and the high matching degree between the two-dimensional Bi2O2Se and the mica substrate, the prepared nanosheet structure has almost no mismatch strain and internal stress. For functional materials, the microstructure and lattice strain of the material have a significant impact on its functional properties. The preparation of low-dimensional materials with different morphologies and the introduction of controllable lattice strain can often greatly improve the functional properties of functional materials. Theoretical speculation shows that strain will cause the central atoms of the two-dimensional Bi2O2Se single crystal to shift, resulting in ferroelectricity, and when the lattice strain exceeds 7%, the two-dimensional Bi2O2Se single crystal will transform from an indirect band gap semiconductor to a direct band gap semiconductor, indicating that lattice strain is very important for the performance research of two-dimensional Bi2O2Se single crystals.

[0003] At present, for two-dimensional Bi2O2Se single crystals that mainly exist in low-dimensional nanosheet structures, the generation of strain usually requires transferring them to a flexible substrate (such as PDMS), and then using a force loading platform to compress or stretch to apply stress, thereby generating lattice strain. In the process of applying stress, on the one hand, it will cause a certain degree of damage to the sample; on the other hand, the strain generation of nanosheets is somewhat random and has poor repeatability, and it is difficult to stably achieve a lattice strain of more than 5%. At present, there is no technology that can prepare two-dimensional Bi2O2Se single crystals with high lattice biaxial tensile strain, and its theoretical strain ferroelectricity has not yet been confirmed.

[0004] Based on this, the present invention proposes a two-dimensional Bi2O2Se single crystal with uniform biaxial tensile strain and a preparation method thereof, realizes the growth of a high-strain two-dimensional Bi2O2Se lattice structure with uniform biaxial stretching, and tests the ferroelectricity of the sample. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a two-dimensional Bi2O2Se single crystal with biaxial tensile strain and a preparation method thereof in view of the above-mentioned deficiencies in the prior art. The biaxial tensile strain of the two-dimensional Bi2O2Se single crystal lattice reaches 2.8-8%, and the preparation process is controllable, the sample is less damaged, and the yield is high.

[0006] In order to solve the above technical problems, the technical solution provided by the present invention is:

[0007] Provided is a two-dimensional Bi2O2Se single crystal with biaxial tensile strain. The two-dimensional Bi2O2Se single crystal has a square nanosheet structure. The square nanosheets grow in parallel arrangement. The biaxial tensile strain is 2.8-8%.

[0008] According to the above scheme, the lateral size of the square nanosheet is 5 to 10 μm and the thickness is 10 to 100 nm.

[0009] The present invention also provides a method for preparing the above-mentioned two-dimensional Bi2O2Se single crystal with biaxial tensile strain: using a MgO substrate or a SrTiO3 substrate as a substrate, Bi2O3 powder and Bi2Se3 powder as precursors, and argon as a carrier gas, a chemical vapor deposition method is used to prepare a two-dimensional Bi2O2Se single crystal with biaxial tensile strain on the substrate surface.

[0010] According to the above scheme, the preparation method comprises the following steps:

[0011] 1) Using a chemical vapor deposition device with two heating zones, the two heat source zones are 14 to 18 cm apart, placing the substrate in the downstream heating zone, placing the Bi2O3 powder and the Bi2Se3 powder in different porcelain boats, and then placing the porcelain boat containing the Bi2O3 powder in the upstream heating zone of the chemical vapor deposition device, and placing the porcelain boat containing the Bi2Se3 powder upstream of the Bi2O3 powder;

[0012] 2) The chemical vapor deposition equipment is evacuated, and then argon gas is introduced for chemical vapor deposition to prepare a two-dimensional Bi2O2Se single crystal with biaxial tensile strain on the substrate surface.

[0013] According to the above scheme, in step 1), the purity of the Bi2O3 powder is above 99.999wt%, the purity of the Bi2Se3 powder is above 99.999wt%, and the mass ratio of the Bi2O3 powder to the Bi2Se3 powder is 1.5 to 5:1.

[0014] According to the above scheme, in step 1), the porcelain boat containing Bi2O3 powder is 4 to 8 cm away from the porcelain boat containing Bi2Se3 powder.

[0015] According to the above scheme, the MgO substrate in step 1) is a (100) oriented MgO substrate with a lattice parameter of a=b=c=0.419nm; the SrTiO3 substrate is a (100) oriented SrTiO3 substrate with a lattice parameter of a=b=0.391nm.

[0016] According to the above scheme, in step 2), the purity of argon gas is above 99.99 vol%, and the flow rate of argon gas is 100-200 sccm.

[0017] According to the above scheme, the chemical vapor deposition process conditions in step 2) are: the deposition pressure is 300-500Torr, the upstream heating zone is heated to 650-750°C at a heating rate of 10-15°C / min at room temperature, the downstream heating zone is heated to 550-650°C at a heating rate of 8-13°C / min, and the two heating zones are made to reach the target temperature at the same time, and then kept warm for 5-20 minutes. By controlling the deposition time, the thickness control within the range of 10-100nm can be achieved.

[0018] According to the above scheme, the preparation method of the present invention also includes the following steps: uniformly spin-coating a polymethyl methacrylate solution on the surface of one side of the MgO substrate on which the two-dimensional Bi2O2Se single crystal is grown, heating to solidify the polymethyl methacrylate, then peeling off the polymethyl methacrylate on the surface of the MgO substrate together with the two-dimensional Bi2O2Se single crystal wrapped therein, and finally using a solvent to dissolve and remove the polymethyl methacrylate to obtain a two-dimensional Bi2O2Se single crystal with biaxial tensile strain.

[0019] According to the above scheme, the polymethyl methacrylate solution is obtained by dissolving polymethyl methacrylate in anisole, and the concentration is 0.1-0.3 g / mL.

[0020] According to the above scheme, the solvent is acetone.

[0021] The present invention also includes the application of the above two-dimensional Bi2O2Se single crystal with biaxial tensile strain in ferroelectric storage materials.

[0022] The beneficial effects of the present invention are as follows: 1. The biaxial tensile strain of the two-dimensional Bi2O2Se single crystal provided by the present invention is as high as 2.8-8%, and the sample shows ferroelectricity predicted in theoretical research, which has broad application prospects in ferroelectric storage materials. 2. The preparation method of the present invention can adjust the biaxial tensile strain rate of the two-dimensional Bi2O2Se single crystal through substrate design according to the requirements of lattice distortion, and can achieve non-destructive and controllable lattice strain of the two-dimensional Bi2O2Se single crystal with excellent repeatability. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 A schematic diagram of a chemical vapor deposition apparatus used in Example 1 of the present invention;

[0024] Figure 2 SEM (a) and AFM (b, c) images of the two-dimensional Bi2O2Se single crystal prepared on the MgO substrate in Example 1

[0025] Figure 3 AC-TEM image of the MgO substrate prepared in Example 1 and the two-dimensional Bi2O2Se single crystal on its surface;

[0026] Figure 4 This is a ferroelectric test diagram of Bi2O2Se with biaxial tensile strain prepared in Example 1;

[0027] Figure 5 This is an optical microscope image of the two-dimensional Bi2O2Se single crystal with biaxial tensile strain prepared in Example 3. DETAILED DESCRIPTION

[0028] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below with reference to the accompanying drawings.

[0029] Example 1

[0030] A method for preparing a two-dimensional Bi2O2Se single crystal, the specific steps are as follows:

[0031] 1) The MgO (100) substrate was ultrasonically cleaned with ethanol, acetone and deionized water for 10 min respectively, dried with nitrogen and placed in the downstream heat source area of ​​the chemical vapor deposition equipment. The schematic diagram of the chemical vapor deposition device is shown in Figure 1 As shown, the upstream and downstream heat source areas are 16 cm apart, 0.4 g Bi2O3 powder (99.999 wt%, purchased from Alfa Aesar) and 0.2 g Bi2Se3 powder (99.999 wt%, purchased from Alfa Aesar) are placed in different porcelain boats, the porcelain boat containing Bi2O3 powder is placed in the upstream heat source area of ​​the chemical vapor deposition equipment, and the porcelain boat containing Bi2Se3 powder is placed 6 cm upstream of the Bi2O3 powder;

[0032] 2) The chemical vapor deposition equipment was evacuated to a pressure below 10Pa, and then argon gas with a purity of 99.99vol% was introduced at a flow rate of 400sccm for 20min to clean the pipeline. The gas flowed through a porcelain boat containing Bi2Se3 powder, a porcelain boat containing Bi2O3 powder and a MgO(100) substrate in turn. Then, the argon flow rate was adjusted to 200sccm, and the deposition pressure was controlled to 350Torr. Then, the power of the upstream heat source zone and the downstream heat source zone was turned on. The upstream heat source zone was heated to 750°C and the downstream heat source zone was heated to 650°C for 50min, and the upstream and downstream heat source zones reached the target temperature at the same time. Then, the temperature was kept at this temperature for 20min to obtain a two-dimensional Bi2O2Se single crystal with biaxial tensile strain on the MgO(100) substrate.

[0033] 3) After the substrate is cooled naturally, it is taken out and a polymethyl methacrylate (PMMA, purchased from Aladdin, cas number: 9011-14-7) anisole solution (concentration of 0.1 g / mL) is evenly spin-coated on the surface of one side where the two-dimensional Bi2O2Se single crystal is grown. Then, it is heated at 160°C for 10 min to volatilize the anisole and solidify the polymethyl methacrylate. Then, the polymethyl methacrylate on the surface of the MgO substrate together with the two-dimensional Bi2O2Se single crystal wrapped therein is peeled off. Finally, hot acetone is used to dissolve and remove the polymethyl methacrylate to obtain a two-dimensional Bi2O2Se single crystal with biaxial tensile strain.

[0034] Figure 2 The SEM (a) and AFM (b, c) images of the two-dimensional Bi2O2Se single crystal prepared on the MgO substrate in this embodiment. It can be seen from the SEM image that the prepared two-dimensional Bi2O2Se single crystal is a square nanosheet structure. The nanosheets are regularly arranged with a side length of 4μm. It can be seen from the AFM image that the thickness of the two-dimensional Bi2O2Se single crystal nanosheet is 10-100nm and the surface is flat and smooth.

[0035] Figure 3 AC-TEM images of the samples prepared in this embodiment (MgO substrate and two-dimensional Bi2O2Se single crystal on its surface), Figure a corresponds to the high-resolution projection image of the sample cross section, and Figure b corresponds to the lattice diffraction image of the sample cross section. As can be seen from Figure a, the two-dimensional Bi2O2Se grows epitaxially on the MgO substrate, and its lattice parameter is restricted by the substrate and stretched to 0.419nm, which is consistent with the lattice parameter of the MgO substrate, and the lattice is stretched uniformly. As can be seen from Figure b, the lattice diffraction of the sample cross section only has the same crystal band axis, indicating that MgO and Bi2O2Se grow in the form of a eutectic lattice.

[0036] The lattice parameter of the two-dimensional Bi2O2Se single crystal with biaxial tensile strain prepared in this embodiment is 0.419nm, while the lattice parameter of the two-dimensional Bi2O2Se single crystal standard is 0.388nm. According to the biaxial tensile strain rate calculation formula:

[0037]

[0038] The calculated biaxial tensile strain (Δε) is 8.0%. S(Bi2O2Se) is the lattice parameter of the two-dimensional Bi2O2Se single crystal product, and C(Bi2O2Se) is the lattice parameter of the two-dimensional Bi2O2Se single crystal standard product.

[0039] Figure 4 This is a ferroelectric test diagram of Bi2O2Se with biaxial tensile strain prepared in this embodiment, which was tested by piezoelectric force microscopy (PFM). Figure a corresponds to the butterfly curve of the ferroelectric test of Bi2O2Se with biaxial tensile strain, and Figure b corresponds to the hysteresis loop of the ferroelectric test. It can be seen from the figure that the sample has spontaneous polarization phenomenon, and domain reversal occurs with the change of voltage, accompanied by the inverse piezoelectric effect, which successfully verifies the strain ferroelectricity of two-dimensional Bi2O2Se that exists at the theoretical level.

[0040] Example 2

[0041] A method for preparing a two-dimensional Bi2O2Se single crystal, the specific steps are as follows:

[0042] 1) The MgO (100) substrate was ultrasonically cleaned with ethanol, acetone and deionized water for 10 min respectively, dried with nitrogen and placed in the center of the downstream heat source of the chemical vapor deposition system, 0.3 g Bi2O3 powder and 0.1 g Bi2Se3 powder were placed in different porcelain boats, the porcelain boat containing Bi2O3 powder was placed in the center of the upstream heat source of the chemical vapor deposition system, and the porcelain boat containing Bi2Se3 powder was placed 6 cm below the Bi2O3 powder;

[0043] 2) The chemical vapor deposition system was evacuated to a pressure below 10Pa, and then high-purity argon gas was introduced at a flow rate of 400sccm for 20min to clean the pipeline, and then the argon flow rate was adjusted to 100sccm, and the deposition pressure was controlled to 400Torr. Then, the power of the upstream heat source center and the downstream heat source center was turned on, and the temperature of the upstream heat source center was raised to 700°C and the temperature of the downstream heat source center was raised to 600°C for 50min, and then kept warm for 10min to obtain a two-dimensional Bi2O2Se single crystal with high biaxial tensile strain on the MgO (100) substrate;

[0044] 3) After the substrate is naturally cooled, it is taken out and a polymethyl methacrylate anisole solution (concentration of 0.1 g / mL) is evenly spin-coated on the surface of one side where the two-dimensional Bi2O2Se single crystal is grown. The anisole is then heated at 160°C for 10 min to volatilize the anisole and solidify the polymethyl methacrylate. The polymethyl methacrylate on the surface of the MgO substrate and the two-dimensional Bi2O2Se single crystal wrapped therein are then peeled off. Finally, hot acetone is used to dissolve and remove the polymethyl methacrylate to obtain a two-dimensional Bi2O2Se single crystal with biaxial tensile strain.

[0045] The morphology of the two-dimensional Bi2O2Se single crystal with biaxial tensile strain prepared in this embodiment is similar to that of the product in Example 1.

[0046] Example 3

[0047] A method for preparing a two-dimensional Bi2O2Se single crystal, the specific steps are as follows:

[0048] 1) The SrTiO3 (100) substrate was ultrasonically cleaned with ethanol, acetone and deionized water for 10 min respectively, dried with nitrogen and placed in the center of the downstream heat source of the chemical vapor deposition system, 0.2 g Bi2O3 powder and 0.1 g Bi2Se3 powder were placed in different porcelain boats, the porcelain boat containing Bi2O3 powder was placed in the center of the upstream heat source of the chemical vapor deposition system, and the porcelain boat containing Bi2Se3 powder was placed 6 cm below the Bi2O3 powder;

[0049] 2) The chemical vapor deposition system was evacuated to a pressure below 10Pa, and then high-purity argon gas was introduced at a flow rate of 400sccm for 20min to clean the pipeline, and then the argon flow rate was adjusted to 150sccm, and the deposition pressure was controlled to 200Torr. Then, the power of the upstream heat source center and the downstream heat source center was turned on, and the temperature of the upstream heat source center was raised to 650°C and the temperature of the downstream heat source center was raised to 550°C for 50min, and then kept warm for 15min to obtain a two-dimensional Bi2O2Se single crystal with high biaxial tensile strain on a SrTiO3(100) substrate;

[0050] 3) After the substrate is naturally cooled, it is taken out and a polymethyl methacrylate anisole solution (concentration of 0.1 g / mL) is evenly spin-coated on the surface of one side where the two-dimensional Bi2O2Se single crystal is grown. The anisole is then heated at 160°C for 10 min to volatilize the anisole and solidify the polymethyl methacrylate. The polymethyl methacrylate on the surface of the MgO substrate and the two-dimensional Bi2O2Se single crystal wrapped therein are then peeled off. Finally, hot acetone is used to dissolve and remove the polymethyl methacrylate to obtain a two-dimensional Bi2O2Se single crystal with biaxial tensile strain.

[0051] Figure 5This is an optical microscope image of a two-dimensional Bi2O2Se single crystal with biaxial tensile strain prepared on a SrTiO3(100) substrate in this embodiment. It can be seen from the figure that the two-dimensional Bi2O2Se is neatly and regularly arranged on the surface of the SrTiO3(100) substrate and has the same orientation, which indicates that Bi2O2Se is also grown epitaxially on the SrTiO3(100) substrate, and the lattice parameters are consistent with the lattice parameters of the SrTiO3(100) substrate (a=b=0.391nm). After testing, the strain rate of the two-dimensional Bi2O2Se single crystal prepared in this embodiment is 2.8%, and it also has ferroelectricity.

Claims

1. A two-dimensional Bi2O2Se single crystal with biaxial tensile strain, characterized in that: The two-dimensional Bi2O2Se single crystal with biaxial tensile strain is prepared on the surface of a substrate using a MgO substrate as a substrate by chemical vapor deposition. The two-dimensional Bi2O2Se single crystal has a square nanosheet structure, the square nanosheets are arranged and grown in parallel, the biaxial tensile strain is 8%, the lateral size of the square nanosheets is 5-10 μm, and the thickness is 10-100 nm.

2. A method for preparing a two-dimensional Bi2O2Se single crystal with biaxial tensile strain according to claim 1, characterized in that: Using MgO substrate as substrate, Bi2O3 powder and Bi2Se3 powder as precursors, and argon as carrier gas, chemical vapor deposition method was used to prepare two-dimensional Bi2O2Se single crystals with biaxial tensile strain on the substrate surface.

3. The method for preparing a two-dimensional Bi2O2Se single crystal with biaxial tensile strain according to claim 2, characterized in that: The preparation method comprises the following steps: 1) Use a chemical vapor deposition device with two heating zones, with the two heat source zones 14-18 cm apart. Place the substrate in the downstream heating zone, put the Bi2O3 powder and Bi2Se3 powder in different porcelain boats, and then place the porcelain boat containing the Bi2O3 powder in the upstream heating zone of the chemical vapor deposition device, and place the porcelain boat containing the Bi2Se3 powder upstream of the Bi2O3 powder. 2) The chemical vapor deposition equipment is evacuated, and then argon gas is introduced for chemical vapor deposition to prepare a two-dimensional Bi2O2Se single crystal with biaxial tensile strain on the substrate surface.

4. The method for preparing a two-dimensional Bi2O2Se single crystal with biaxial tensile strain according to claim 3, characterized in that: Step 1) The purity of the Bi2O3 powder is above 99.999wt%, the purity of the Bi2Se3 powder is above 99.999wt%, and the mass ratio of the Bi2O3 powder to the Bi2Se3 powder is 1.5-5:

1.

5. The method for preparing a two-dimensional Bi2O2Se single crystal with biaxial tensile strain according to claim 3, characterized in that: Step 1) The porcelain boat containing Bi2O3 powder is 4~8 cm away from the porcelain boat containing Bi2Se3 powder.

6. The method for preparing a two-dimensional Bi2O2Se single crystal with biaxial tensile strain according to claim 3, characterized in that: Step 1) The MgO substrate is a (100) oriented MgO substrate with a lattice parameter of a = b = c = 0.419 nm.

7. The method for preparing a two-dimensional Bi2O2Se single crystal with biaxial tensile strain according to claim 3, characterized in that: Step 2) The purity of argon gas is above 99.99 vol%, and the flow rate of argon gas is 100-200 sccm.

8. The method for preparing a two-dimensional Bi2O2Se single crystal with biaxial tensile strain according to claim 3, characterized in that: Step 2) The chemical vapor deposition process conditions are as follows: the deposition gas pressure is 300~500Torr, the upstream heating zone is heated to 650~750℃ at a heating rate of 10~15℃ / min at room temperature, and the downstream heating zone is heated to 550~650℃ at a heating rate of 8~13℃ / min, and the two heating zones are made to reach the target temperature at the same time, and then kept warm for 5~20 minutes.

9. Application of the two-dimensional Bi2O2Se single crystal with biaxial tensile strain as claimed in claim 1 in ferroelectric storage materials.

Citation Information

Patent Citations

  • Selenium bismuth oxide in-situ thermal oxide top gate field effect transistor and preparation method thereof

    CN113782593A

  • Preparation method of large-area bismuth-oxygen-selenium film and application of large-area bismuth-oxygen-selenium film in ultra-stable and wide-spectrum imaging detector

    CN116555901A